Vibrational dynamics in the light-harvesting complexes of the photosynthetic bacterium Rhodobacter sphaeroides - Chachisvilis, M.; Pullerits, T.; Jones, M. R.; Hunter, C. N.; Sundström, V. (Chemical Physics Letters, 1994)
Using ≈ 40 fs pulses we have observed coherent nuclear motions in intact membrane bound photosynthetic light-harvesting pigment-protein complexes. Computer simulations based on the harmonic Franck-Condon approximation and the Langevin equation describe qualitatively well the temperature and pulse wavelength dependence of the oscillations, indicating the possibility to observe higher harmonics of the fundamental frequency of the mode when exciting and probing in the blue side of the spectrum.